2011
DOI: 10.1097/pas.0b013e3182002777
|View full text |Cite
|
Sign up to set email alerts
|

MYB Expression and Translocation in Adenoid Cystic Carcinomas and Other Salivary Gland Tumors With Clinicopathologic Correlation

Abstract: Background Adenoid cystic carcinoma is a locally aggressive salivary gland neoplasm which has a poor long term prognosis. A chromosomal translocation involving the genes encoding the transcription factors MYB and NFIB has been recently discovered in these tumors. Methods MYB translocation and protein expression was studied in 37 adenoid cystic carcinomas, 112 other salivary gland neoplasms, and 409 non salivary gland neoplasms by FISH and immunohistochemistry. MYB translocation and expression status in adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
244
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(269 citation statements)
references
References 9 publications
(10 reference statements)
16
244
5
Order By: Relevance
“…Though there is some disagreement in the literature regarding the percent of ACC tumors harboring this molecular alteration, most subsequent studies have shown that the majority of ACC have a disrupted MYB gene and/ or evidence of a MYB-NFIB fusion RNA transcript [32][33][34][35][36]. One of the largest independent cohorts separate from the Stenman group came from a study at Stanford University, where 37 cases of ACC were studied by fluorescence in situ hybridization (FISH) of the MYB and NFIB loci, with 65 % of cases showing abnormalities of these loci [34].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though there is some disagreement in the literature regarding the percent of ACC tumors harboring this molecular alteration, most subsequent studies have shown that the majority of ACC have a disrupted MYB gene and/ or evidence of a MYB-NFIB fusion RNA transcript [32][33][34][35][36]. One of the largest independent cohorts separate from the Stenman group came from a study at Stanford University, where 37 cases of ACC were studied by fluorescence in situ hybridization (FISH) of the MYB and NFIB loci, with 65 % of cases showing abnormalities of these loci [34].…”
Section: Introductionmentioning
confidence: 99%
“…One of the largest independent cohorts separate from the Stenman group came from a study at Stanford University, where 37 cases of ACC were studied by fluorescence in situ hybridization (FISH) of the MYB and NFIB loci, with 65 % of cases showing abnormalities of these loci [34]. An example of an ACC tumor displaying typical FISH findings for a broken-apart MYB gene locus is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tubular variant of adenoid cystic carcinoma features an infiltrative pattern of growth frequently associated with perineural invasion, which was not observed in the case described above. Assessing the presence of MYB expression, which occurs in a subset of adenoid cystic carcinomas, via immunohistochemical study may be helpful in ruling out this differential [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a recurrent t (6; 9) (q22-23; p23-24) translocation was found in ACCs, that ultimately results in the fusion of MYB and NFIB gene. This fusion leads to the deregulation of the expression of MYB, and it is likely to be a critical step in oncogenesis for ACC [11].…”
Section: Immunohistochemically Accs Can Be Divided Into Two Groupsmentioning
confidence: 99%